Investigation on Effective Neutralization Process of Acid Mine Drainage Containing High Amount of Mn and Zn by Additions of δ-MnO2 Adsorbent and Oxidizing Agent - Shigeshi FUCHIDA; Shota TAJIMA; Chiharu TOKORO (Journal of MMIJ, 2022)
This study examined effective removal methods for high amounts of manganese (Mn) and zinc (Zn) in acid mine drainage (AMD) by addition of different neutralizing agents (NaOH and NaClO) and synthesized birnessite (δ-MnO2) using two-type AMD samples which Mn and Zn concentrations were 778 and 410 mg L−1 for A mine and 18.0 and 5.51 mg L−1 for B mines, respectively. The precipitation mechanism of these metal ions was investigated by geochemical modeling (PHREEQC) and X-ray absorption near edge structure (XANES) analysis. Mn concentrations were below the effluent standard (10 mg L−1) at pH 9–10 with the NaOH neutralization, whereas it was accomplished at lower pH (6–7) condition with the NaClO addition; it could act as an oxidizing agent, resulting that most of Mn precipitated as δ-MnO2. Zn concentrations decreased below the effluent standard (2 mg L−1) at pH 8–9 using both neutralizing agents. XANES analysis results indicated Zn was removed by the surface complexation formation on manganite and δ-MnO2 surface. More effective removal of Mn and Zn from AMD was found around pH 6 when a sufficient amount of δ-MnO2 was added to both AMD before the NaOH neutralization; a geochemical model coupling charge distribution multisite ion complexation revealed the triple-corner-sharing on δ-MnO2 was the most reasonable mechanism. Our result suggests that the presence of sufficient δ-MnO2 was the most effective for high Mn and Zn contents AMD treatment; however, ferrous ion (Fe2+) can inhibit the adsorption reaction and decompose δ-MnO2. Thus, pre-precipitation of Fe2+ is required to enhance the effect of δ-MnO2 on Mn and Zn removals from AMD.